Perancangan Sistem Keamanan Pada Smart Home Menggunakan Voice Command Dengan Konektivitas Bluetooth - Mohammad Kholili Adi Putra; Sabriansyah Rizqika Akbar; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Home security systems are a necessity for every home, for instance home alarm that is still many used. But, along with the development of the present technology, home security system has various kinds and will keep moving for the development. The lack of security level has the impact of theft and burglary in house. Sometimes, the house owner thinks that he has locked his house, but in reality, the burglary case in house now is due to the easy thing for the burglar to open the installed lock door by using a wire or other imitated keys. Based on the problem, it is need to add the door safety that can be controlled by using Android smartphone with voice command. Voice command recognition system is one concept of controlling the electronic devices by using voice command. By applying the Google Voice Command technology, the system can turn on and turn of the home equipment by the support of microcontroller and Bluetooth. The research explains the design of home security system using voice command that is used by the android application with the Bluetooth connection to control the solenoid door lock, PIR, and RTC. From the test result, the system has value of success 93,33% in functional testing and processing testing the user input in controlling solenoid door lock. In sensor PIR testing, the value of success is up to 100%. The next test is RTC, the value of success is up to 100%.